2009
DOI: 10.21273/hortsci.44.5.1323
|View full text |Cite
|
Sign up to set email alerts
|

Seed Preconditioning with Natural and Synthetic Antioxidants Induces Drought Tolerance in Tomato Seedlings

Abstract: There is strong evidence that Ambiol® (a derivative of 5-hydroxybenzimazole) promotes drought tolerance in many plants; it is often suggested that this is the result of its antioxidant properties. Recent evidence has also shown that several natural antioxidants promote carrot germination under drought stress. Thus, it was hypothesized that seed preconditioning using natural antioxidants might confer drought tolerance. Ambiol®, ascorbic acid, β-carotene, lutein, and lycopene were chosen as antioxidants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 20 publications
3
14
1
Order By: Relevance
“…In all tomato seedlings, there was a consistent response with an increase in growth and photosynthesis conferred by Ambiol to tomato seedlings under drought. This was similar to previous studies with tomato seedlings (MacDonald et al, 2008(MacDonald et al, , 2009 as well as other species (Darlington et al, 1996;Islam et al, 2003;Rajasekaran and Blake, 2002) involving other species. Typically, a decrease in transpiration has also been reported in other species, which has often been linked to the drought-mitigating effects of Ambiol.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In all tomato seedlings, there was a consistent response with an increase in growth and photosynthesis conferred by Ambiol to tomato seedlings under drought. This was similar to previous studies with tomato seedlings (MacDonald et al, 2008(MacDonald et al, , 2009 as well as other species (Darlington et al, 1996;Islam et al, 2003;Rajasekaran and Blake, 2002) involving other species. Typically, a decrease in transpiration has also been reported in other species, which has often been linked to the drought-mitigating effects of Ambiol.…”
Section: Discussionsupporting
confidence: 92%
“…Recent advances have also found that Ambiol is very effective at promoting drought tolerance in tomato seedlings and have focused on understanding the regulatory pathway of Ambiol. MacDonald et al (2008, 2009 reported that preconditioning with 10 mgÁL -1 Ambiol increased root growth, shoot growth, leaf expansion, photosynthesis, and water use efficiency (WUE) in tomato seedlings under drought stress. It was also found that Ambiol preconditioning invokes certain proteins in the seed, both before and after germination.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Physiological conditioning is a technique of controlled hydration of seeds, which allows the activation of the metabolic processes of germination and avoids primary root production, favoring uniformization and better performance of the plants in the field (MacDonald & Lada, 2009). This technique allows the use of reserves and synthesis of metabolites necessary to germination, leading to faster seed germination, reducing the time of exposure to unfavorable conditions, such as attacks by microorganisms and water deficit, among others (Marcos Filho, 2015).…”
Section: Introductionmentioning
confidence: 99%